Use of Serratia marcescens for Feed Processing: Broiler Performance and Pathogenicity Assay - Mahata , Maria Endo; Lestari, Ichni `; Dharma, Abdi; H., Irsan Ryanto; Armenia; Rizal, Yose (International Journal of Poultry Science, 2012)
Serratia marcescens is a bacterium able to produce chitinase for degrading chitin. Broiler chickens can not digest significant amounts of chitin because they produce very little chitinase in their digestive tract. Therefore, broiler feed containing chitin must be processed first with chitinase. Serratia marcescens is an opportunistic pathogenic bacterium and a pathogenicity test is required before using its chitinase for processing of feed containing chitin. An experiment was conducted by using broiler. A split-plot, completely randomized design is used in this experiment. The Serratia marcescens dosages (0, 40, 80, 160 and 320 mg/kg body weight) were the main plot and observation lengths (2, 4, 8, 16 and 22 days) were the sub plot factor. The ration for different treatments had the same protein (23%) and energy (3000 kkal/kg) content. Feed consumption, average daily gain, body temperature and mortality were parameters. Results showed that feed consumption and average daily gain were significantly affected (p